diff --git a/library/data/list/basic.lean b/library/data/list/basic.lean index fa451558d..cfd98813b 100644 --- a/library/data/list/basic.lean +++ b/library/data/list/basic.lean @@ -11,15 +11,15 @@ import tools.tactic import data.nat -import logic +import logic tools.helper_tactics -- import if -- for find using nat using eq_ops +using helper_tactics namespace list - -- Type -- ---- @@ -52,24 +52,23 @@ list_rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s infixl `++` : 65 := concat -theorem nil_concat (t : list T) : nil ++ t = t := refl _ +theorem nil_concat {t : list T} : nil ++ t = t -theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _ +theorem cons_concat {x : T} {s t : list T} : (x :: s) ++ t = x :: (s ++ t) -theorem concat_nil (t : list T) : t ++ nil = t := -list_induction_on t (refl _) +theorem concat_nil {t : list T} : t ++ nil = t := +list_induction_on t rfl (take (x : T) (l : list T) (H : concat l nil = l), - show concat (cons x l) nil = cons x l, from H ▸ refl _) + show concat (cons x l) nil = cons x l, from H ▸ rfl) -theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := -list_induction_on s (refl _) +theorem concat_assoc {s t u : list T} : s ++ t ++ u = s ++ (t ++ u) := +list_induction_on s rfl (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc - concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ - ... = cons x (concat l (concat t u)) : { H } - ... = concat (cons x l) (concat t u) : refl _) - + concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : rfl + ... = cons x (concat l (concat t u)) : {H} + ... = concat (cons x l) (concat t u) : rfl) -- Length -- ------ @@ -78,9 +77,9 @@ definition length : list T → ℕ := list_rec 0 (fun x l m, succ m) theorem length_nil : length (@nil T) = 0 := rfl -theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := rfl +theorem length_cons {x : T} {t : list T} : length (x :: t) = succ (length t) -theorem length_concat (s t : list T) : length (s ++ t) = length s + length t := +theorem length_concat {s t : list T} : length (s ++ t) = length s + length t := list_induction_on s (calc length (concat nil t) = length t : rfl @@ -90,99 +89,95 @@ list_induction_on s assume H : length (concat s t) = length s + length t, calc length (concat (cons x s) t ) = succ (length (concat s t)) : rfl - ... = succ (length s + length t) : { H } + ... = succ (length s + length t) : {H} ... = succ (length s) + length t : {add_succ_left⁻¹} ... = length (cons x s) + length t : rfl) -- add_rewrite length_nil length_cons - -- Append -- ------ definition append (x : T) : list T → list T := list_rec [x] (fun y l l', y :: l') -theorem append_nil (x : T) : append x nil = [x] := refl _ +theorem append_nil {x : T} : append x nil = [x] -theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _ +theorem append_cons {x y : T} {l : list T} : append x (y :: l) = y :: (append x l) -theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] := refl _ +theorem append_eq_concat {x : T} {l : list T} : append x l = l ++ [x] -- add_rewrite append_nil append_cons - -- Reverse -- ------- definition reverse : list T → list T := list_rec nil (fun x l r, r ++ [x]) -theorem reverse_nil : reverse (@nil T) = nil := refl _ +theorem reverse_nil : reverse (@nil T) = nil -theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = append x (reverse l) := refl _ +theorem reverse_cons {x : T} {l : list T} : reverse (x :: l) = append x (reverse l) -theorem reverse_singleton (x : T) : reverse [x] = [x] := refl _ +theorem reverse_singleton {x : T} : reverse [x] = [x] -theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) := -list_induction_on s (symm (concat_nil _)) +theorem reverse_concat {s t : list T} : reverse (s ++ t) = (reverse t) ++ (reverse s) := +list_induction_on s (concat_nil⁻¹) (take x s, assume IH : reverse (s ++ t) = concat (reverse t) (reverse s), calc - reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : refl _ - ... = reverse t ++ reverse s ++ [x] : {IH} - ... = reverse t ++ (reverse s ++ [x]) : concat_assoc _ _ _ - ... = reverse t ++ (reverse (x :: s)) : refl _) + reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : rfl + ... = reverse t ++ reverse s ++ [x] : {IH} + ... = reverse t ++ (reverse s ++ [x]) : concat_assoc + ... = reverse t ++ (reverse (x :: s)) : rfl) -theorem reverse_reverse (l : list T) : reverse (reverse l) = l := -list_induction_on l (refl _) +theorem reverse_reverse {l : list T} : reverse (reverse l) = l := +list_induction_on l rfl (take x l', assume H: reverse (reverse l') = l', show reverse (reverse (x :: l')) = x :: l', from calc - reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : refl _ - ... = reverse [x] ++ reverse (reverse l') : reverse_concat _ _ - ... = [x] ++ l' : { H } - ... = x :: l' : refl _) + reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : rfl + ... = reverse [x] ++ reverse (reverse l') : reverse_concat + ... = [x] ++ l' : {H} + ... = x :: l' : rfl) -theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) := -list_induction_on l (refl _) +theorem append_eq_reverse_cons {x : T} {l : list T} : append x l = reverse (x :: reverse l) := +list_induction_on l rfl (take y l', assume H : append x l' = reverse (x :: reverse l'), calc - append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _ - ... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)} - ... = reverse (x :: (reverse (y :: l'))) : refl _) + append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat + ... = concat (reverse (reverse (y :: l'))) [ x ] : {reverse_reverse⁻¹} + ... = reverse (x :: (reverse (y :: l'))) : rfl) -- Head and tail -- ------------- -definition head (x0 : T) : list T → T := list_rec x0 (fun x l h, x) +definition head (x : T) : list T → T := list_rec x (fun x l h, x) -theorem head_nil (x0 : T) : head x0 (@nil T) = x0 := refl _ +theorem head_nil {x : T} : head x (@nil T) = x -theorem head_cons (x : T) (x0 : T) (t : list T) : head x0 (x :: t) = x := refl _ +theorem head_cons {x x' : T} {t : list T} : head x' (x :: t) = x -theorem head_concat (s t : list T) (x0 : T) : s ≠ nil → (head x0 (s ++ t) = head x0 s) := +theorem head_concat {s t : list T} {x : T} : s ≠ nil → (head x (s ++ t) = head x s) := list_cases_on s - (take H : nil ≠ nil, absurd (refl nil) H) - (take x s, - take H : cons x s ≠ nil, + (take H : nil ≠ nil, absurd rfl H) + (take x s, take H : cons x s ≠ nil, calc - head x0 (concat (cons x s) t) = head x0 (cons x (concat s t)) : {cons_concat _ _ _} - ... = x : {head_cons _ _ _} - ... = head x0 (cons x s) : {symm ( head_cons x x0 s)}) + head x (concat (cons x s) t) = head x (cons x (concat s t)) : {cons_concat} + ... = x : {head_cons} + ... = head x (cons x s) : {head_cons⁻¹}) definition tail : list T → list T := list_rec nil (fun x l b, l) -theorem tail_nil : tail (@nil T) = nil := refl _ +theorem tail_nil : tail (@nil T) = nil -theorem tail_cons (x : T) (l : list T) : tail (cons x l) = l := refl _ +theorem tail_cons {x : T} {l : list T} : tail (cons x l) = l -theorem cons_head_tail (x0 : T) (l : list T) : l ≠ nil → (head x0 l) :: (tail l) = l := +theorem cons_head_tail {x : T} {l : list T} : l ≠ nil → (head x l) :: (tail l) = l := list_cases_on l - (assume H : nil ≠ nil, absurd (refl _) H) - (take x l, assume H : cons x l ≠ nil, refl _) - + (assume H : nil ≠ nil, absurd rfl H) + (take x l, assume H : cons x l ≠ nil, rfl) -- List membership -- --------------- @@ -192,11 +187,11 @@ definition mem (x : T) : list T → Prop := list_rec false (fun y l H, x = y ∨ infix `∈` := mem -- TODO: constructively, equality is stronger. Use that? -theorem mem_nil (x : T) : x ∈ nil ↔ false := iff_refl _ +theorem mem_nil {x : T} : x ∈ nil ↔ false := iff_rfl -theorem mem_cons (x : T) (y : T) (l : list T) : mem x (cons y l) ↔ (x = y ∨ mem x l) := iff_refl _ +theorem mem_cons {x y : T} {l : list T} : mem x (cons y l) ↔ (x = y ∨ mem x l) := iff_rfl -theorem mem_concat_imp_or (x : T) (s t : list T) : x ∈ s ++ t → x ∈ s ∨ x ∈ t := +theorem mem_concat_imp_or {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s ∨ x ∈ t := list_induction_on s or_inr (take y s, assume IH : x ∈ s ++ t → x ∈ s ∨ x ∈ t, @@ -205,9 +200,9 @@ list_induction_on s or_inr have H3 : x = y ∨ x ∈ s ∨ x ∈ t, from or_imp_or_right H2 IH, iff_elim_right or_assoc H3) -theorem mem_or_imp_concat (x : T) (s t : list T) : x ∈ s ∨ x ∈ t → x ∈ s ++ t := +theorem mem_or_imp_concat {x : T} {s t : list T} : x ∈ s ∨ x ∈ t → x ∈ s ++ t := list_induction_on s - (take H, or_elim H (false_elim _) (assume H, H)) + (take H, or_elim H false_elim (assume H, H)) (take y s, assume IH : x ∈ s ∨ x ∈ t → x ∈ s ++ t, assume H : x ∈ y :: s ∨ x ∈ t, @@ -218,24 +213,24 @@ list_induction_on s (take H2 : x ∈ s, or_inr (IH (or_inl H2)))) (assume H1 : x ∈ t, or_inr (IH (or_inr H1)))) -theorem mem_concat (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t -:= iff_intro (mem_concat_imp_or _ _ _) (mem_or_imp_concat _ _ _) +theorem mem_concat {x : T} {s t : list T} : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t +:= iff_intro mem_concat_imp_or mem_or_imp_concat -theorem mem_split (x : T) (l : list T) : x ∈ l → ∃s t : list T, l = s ++ (x :: t) := +theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x :: t) := list_induction_on l - (take H : x ∈ nil, false_elim _ (iff_elim_left (mem_nil x) H)) + (take H : x ∈ nil, false_elim (iff_elim_left mem_nil H)) (take y l, assume IH : x ∈ l → ∃s t : list T, l = s ++ (x :: t), assume H : x ∈ y :: l, or_elim H (assume H1 : x = y, exists_intro nil - (exists_intro l (subst H1 (refl _)))) + (exists_intro l (subst H1 rfl))) (assume H1 : x ∈ l, obtain s (H2 : ∃t : list T, l = s ++ (x :: t)), from IH H1, obtain t (H3 : l = s ++ (x :: t)), from H2, have H4 : y :: l = (y :: s) ++ (x :: t), - from subst H3 (refl (y :: l)), + from subst H3 rfl, exists_intro _ (exists_intro _ H4))) -- Find @@ -276,12 +271,12 @@ list_induction_on l -- nth element -- ----------- -definition nth (x0 : T) (l : list T) (n : ℕ) : T := -nat_rec (λl, head x0 l) (λm f l, f (tail l)) n l +definition nth (x : T) (l : list T) (n : ℕ) : T := +nat_rec (λl, head x l) (λm f l, f (tail l)) n l -theorem nth_zero (x0 : T) (l : list T) : nth x0 l 0 = head x0 l := refl _ +theorem nth_zero {x : T} {l : list T} : nth x l 0 = head x l -theorem nth_succ (x0 : T) (l : list T) (n : ℕ) : nth x0 l (succ n) = nth x0 (tail l) n := refl _ +theorem nth_succ {x : T} {l : list T} {n : ℕ} : nth x l (succ n) = nth x (tail l) n end diff --git a/library/data/sigma.lean b/library/data/sigma.lean index 4e901fc77..d18cc966b 100644 --- a/library/data/sigma.lean +++ b/library/data/sigma.lean @@ -28,7 +28,7 @@ section sigma_rec H p theorem dpair_ext (p : sigma B) : dpair (dpr1 p) (dpr2 p) = p := - sigma_destruct p (take a b, refl _) + sigma_destruct p (take a b, rfl) -- Note that we give the general statment explicitly, to help the unifier theorem dpair_eq {a1 a2 : A} {b1 : B a1} {b2 : B a2} (H1 : a1 = a2) (H2 : eq_rec_on H1 b1 = b2) : diff --git a/library/data/sum.lean b/library/data/sum.lean index 111bc023a..9bdb56e74 100644 --- a/library/data/sum.lean +++ b/library/data/sum.lean @@ -71,13 +71,13 @@ rec_on s1 (take a2, show decidable (inl B a1 = inl B a2), from H1 a1 a2) (take b2, have H3 : (inl B a1 = inr A b2) ↔ false, - from iff_intro inl_neq_inr (assume H4, false_elim _ H4), + from iff_intro inl_neq_inr (assume H4, false_elim H4), show decidable (inl B a1 = inr A b2), from decidable_iff_equiv _ (iff_symm H3))) (take b1, show decidable (inr A b1 = s2), from rec_on s2 (take a2, have H3 : (inr A b1 = inl B a2) ↔ false, - from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim _ H4), + from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim H4), show decidable (inr A b1 = inl B a2), from decidable_iff_equiv _ (iff_symm H3)) (take b2, show decidable (inr A b1 = inr A b2), from H2 b1 b2)) diff --git a/library/data/unit.lean b/library/data/unit.lean index 0860b720a..286cc23c2 100644 --- a/library/data/unit.lean +++ b/library/data/unit.lean @@ -16,6 +16,9 @@ notation `⋆`:max := star theorem unit_eq (a b : unit) : a = b := unit_rec (unit_rec (refl ⋆) b) a +theorem unit_eq_star (a : unit) : a = star := +unit_eq a star + theorem unit_inhabited [instance] : inhabited unit := inhabited_mk ⋆ diff --git a/library/logic/axioms/classical.lean b/library/logic/axioms/classical.lean index dcb1ad86a..805cc8043 100644 --- a/library/logic/axioms/classical.lean +++ b/library/logic/axioms/classical.lean @@ -35,9 +35,9 @@ theorem propext {a b : Prop} (Hab : a → b) (Hba : b → a) : a = b := or_elim (prop_complete a) (assume Hat, or_elim (prop_complete b) (assume Hbt, Hat ⬝ Hbt⁻¹) - (assume Hbf, false_elim (a = b) (Hbf ▸ (Hab (eq_true_elim Hat))))) + (assume Hbf, false_elim (Hbf ▸ (Hab (eq_true_elim Hat))))) (assume Haf, or_elim (prop_complete b) - (assume Hbt, false_elim (a = b) (Haf ▸ (Hba (eq_true_elim Hbt)))) + (assume Hbt, false_elim (Haf ▸ (Hba (eq_true_elim Hbt)))) (assume Hbf, Haf ⬝ Hbf⁻¹)) theorem iff_to_eq {a b : Prop} (H : a ↔ b) : a = b := diff --git a/library/logic/classes/decidable.lean b/library/logic/classes/decidable.lean index 5015d1d85..beac1de63 100644 --- a/library/logic/classes/decidable.lean +++ b/library/logic/classes/decidable.lean @@ -44,7 +44,7 @@ or_elim (em a) (assume Ha, Hab Ha) (assume Hna, Hnab Hna) theorem by_contradiction {p : Prop} {Hp : decidable p} (H : ¬p → false) : p := or_elim (em p) (assume H1 : p, H1) - (assume H1 : ¬p, false_elim p (H H1)) + (assume H1 : ¬p, false_elim (H H1)) theorem and_decidable [instance] {a b : Prop} (Ha : decidable a) (Hb : decidable b) : decidable (a ∧ b) := diff --git a/library/logic/core/identities.lean b/library/logic/core/identities.lean index 31529ddab..df0d970ba 100644 --- a/library/logic/core/identities.lean +++ b/library/logic/core/identities.lean @@ -47,7 +47,7 @@ theorem not_not_elim {a : Prop} {D : decidable a} (H : ¬¬a) : a := iff_mp not_not_iff H theorem not_true : (¬true) ↔ false := -iff_intro (assume H, H trivial) (false_elim _) +iff_intro (assume H, H trivial) false_elim theorem not_false : (¬false) ↔ true := iff_intro (assume H, trivial) (assume H H', H') @@ -117,12 +117,12 @@ iff_intro theorem iff_false_intro {a : Prop} (H : ¬a) : a ↔ false := iff_intro (assume H1 : a, absurd H1 H) - (assume H2 : false, false_elim a H2) + (assume H2 : false, false_elim H2) theorem a_neq_a {A : Type} (a : A) : (a ≠ a) ↔ false := iff_intro (assume H, a_neq_a_elim H) - (assume H, false_elim (a ≠ a) H) + (assume H, false_elim H) theorem eq_id {A : Type} (a : A) : (a = a) ↔ true := iff_true_intro (refl a) @@ -135,7 +135,7 @@ iff_intro (assume H, have H' : ¬a, from assume Ha, (H ▸ Ha) Ha, H' (H⁻¹ ▸ H')) - (assume H, false_elim (a ↔ ¬a) H) + (assume H, false_elim H) theorem true_eq_false : (true ↔ false) ↔ false := not_true ▸ (a_iff_not_a true) diff --git a/library/logic/core/prop.lean b/library/logic/core/prop.lean index 1f80d5894..e17f7db63 100644 --- a/library/logic/core/prop.lean +++ b/library/logic/core/prop.lean @@ -18,7 +18,7 @@ abbreviation imp (a b : Prop) : Prop := a → b inductive false : Prop -theorem false_elim (c : Prop) (H : false) : c := +theorem false_elim {c : Prop} (H : false) : c := false_rec c H inductive true : Prop := @@ -36,7 +36,7 @@ theorem not_intro {a : Prop} (H : a → false) : ¬a := H theorem not_elim {a : Prop} (H1 : ¬a) (H2 : a) : false := H1 H2 theorem absurd {a : Prop} {b : Prop} (H1 : a) (H2 : ¬a) : b := -false_elim b (H2 H1) +false_elim (H2 H1) theorem not_not_intro {a : Prop} (Ha : a) : ¬¬a := assume Hna : ¬a, absurd Ha Hna diff --git a/tests/lean/run/sum_bug.lean b/tests/lean/run/sum_bug.lean index c34f0c300..8800de6eb 100644 --- a/tests/lean/run/sum_bug.lean +++ b/tests/lean/run/sum_bug.lean @@ -57,13 +57,13 @@ rec_on s1 (take a2, show decidable (inl B a1 = inl B a2), from H1 a1 a2) (take b2, have H3 : (inl B a1 = inr A b2) ↔ false, - from iff_intro inl_neq_inr (assume H4, false_elim _ H4), + from iff_intro inl_neq_inr (assume H4, false_elim H4), show decidable (inl B a1 = inr A b2), from decidable_iff_equiv _ (iff_symm H3))) (take b1, show decidable (inr A b1 = s2), from rec_on s2 (take a2, have H3 : (inr A b1 = inl B a2) ↔ false, - from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim _ H4), + from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim H4), show decidable (inr A b1 = inl B a2), from decidable_iff_equiv _ (iff_symm H3)) (take b2, show decidable (inr A b1 = inr A b2), from H2 b1 b2))